La identidad nacional en tiempos de globalización - Arias Sandoval, Leonel (2009)
The national identity is a historical and geographical process; it is also dynamic and it is constantly transforming, in other words it is: a subject of change. It is constructed by individuals and different social groups who are born or live in a territory with a homogenizing ideological discourse and a reproducer of an imaginary national and, moreover, the cultural influence is expressed by the interrelationships among other countries, which have been accelerated by the phenomenon of globalization. This last aspect has a profound impact not only in the economic field, but also when sharing information, ideas, values and behaviors that are assimilated by people through behaviors, symbols and meanings that are related to the imitation of foreign cultural models. But there is one point in common in the context of this essay and it is to understand that we are in an evolutionary, dynamic and complex process that is part of the socialization processes that link the daily practices of individuals, through the diversity and cultural exchange.